2021
DOI: 10.3389/frobt.2021.652035
|View full text |Cite
|
Sign up to set email alerts
|

Hurry Up, We Need to Find the Key! How Regulatory Focus Design Affects Children’s Trust in a Social Robot

Abstract: In educational scenarios involving social robots, understanding the way robot behaviors affect children’s motivation to achieve their learning goals is of vital importance. It is crucial for the formation of a trust relationship between the child and the robot so that the robot can effectively fulfill its role as a learning companion. In this study, we investigate the effect of a regulatory focus design scenario on the way children interact with a social robot. Regulatory focus theory is a type of self-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Some cHRI studies investigated the effects of RFT on children interacting with a social robot. Researchers found that children in the prevention condition perceived the robot as more likeable than those assigned to the promotion one [29]; the authors suggested as a possible interpretation that the robot expressed more vulnerability (i.e., fear) in the prevention condition, leading children to perceive it as more likeable and relatable. Nevertheless, children assigned to the promotion condition expressed more happiness and were more engaged with the robot during the interaction than those assigned to the prevention condition [30].…”
Section: B Regulatory Focus Theorymentioning
confidence: 99%
“…Some cHRI studies investigated the effects of RFT on children interacting with a social robot. Researchers found that children in the prevention condition perceived the robot as more likeable than those assigned to the promotion one [29]; the authors suggested as a possible interpretation that the robot expressed more vulnerability (i.e., fear) in the prevention condition, leading children to perceive it as more likeable and relatable. Nevertheless, children assigned to the promotion condition expressed more happiness and were more engaged with the robot during the interaction than those assigned to the prevention condition [30].…”
Section: B Regulatory Focus Theorymentioning
confidence: 99%
“…Following up on our previous research [6], this study aimed to investigate how repeated interactions of a collaborative storytelling game could influence children's perceptions of a social robot. We propose the following RQ:…”
Section: Research Questionsmentioning
confidence: 99%
“…We built a simplified version of the storytelling game developed in [6]. Children created a story with the robot during the interactive storytelling game.…”
Section: A Scenariomentioning
confidence: 99%
See 1 more Smart Citation